Analisis Kinerja Pelabuhan Depapre Sebagai Simpul Tol Laut Dalam Mendukung Distribusi Logistik Di Kabupaten Jayapura - Febriyanti Karimba Pangadongan; Muhammad Asdar; Andi Sitti Chairunnisa (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
A port is said to have a good level of service if the time required for loading and unloading activities is shorter than the specified schedule. In order to smooth the flow of goods, increase the effectiveness of port operational performance, it is necessary to use service performance standards as a benchmark to determine the level of service that can be provided to service users. Depapre Port is one of the ports that plays an important role in the process of progressing economic growth in Papua Province. The availability of facilities and infrastructure at Depapre Port greatly influences the smooth distribution of logistics in the Papua Province region, specifically in areas on the T-19 Route, namely Merauke – Kokas – Sorong – Biak/Korido – Depapre/Jayapura – Sorong – Merauke. Port performance is analyzed using the Decree of the Director General of Sea Transportation Number HK.103/2/18/DJPL-16. This research will discuss the performance of Depapre Port in distributing logistics in the Jayapura Regency area. In addition, this study also identified the factors that influence the performance of Depapre Port by conducting interviews and direct observation of several informants who understand and are involved in port activities, which are divided into 5 categories: Humans, Ship Service Facilities, Environment, Material and Methods and will explained in more depth using cause and effect diagrams. The results of this study will then be evaluated so that an improvement effort can be determined so that the performance of the Depapre port can run normally like other ports in Indonesia.